(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Type 2 diabetes mellitus is a significant health issue throughout the world particularly in SouthEast Asia due to its complications, such as those related to metabolism and the cardiovascular system. Type 2 DM is characterized by insulin resistance and a relative insulin deficiency. A measure of the pancreas’ ability to secrete endogenous insulin is the serum C-peptide concentration. Patients with Type 2 DM and elevated BMI have higher levels of HbA1c and C-peptide. The aim of the study was to evaluate the correlation between C-peptide, HbA1c and BMI in T2 DM patients. Materials and methods: This cross sectional comparative study was conducted in the Department of Biochemistry and the Department of Endocrinology, Chattogram medical college hospital from 1 st July 2018 to 30 June 2019. A total of 150 study populations were enrolled, of which 50 healthy control subjects (Group B) and 100 T2 DM patients (Group A) that met the enrollment criteria. Data were collected by using a pre tested structured questionnaire containing all the variables of interest. The variables studied included age, sex, height, weight, BMI, plasma glucose, C-peptide, HbA1c. Results: The average BMI of the cases in this study was 26.75 kg/m 2 , which was higher than the mean BMI of the controls (23.42 kg/m 2 ). The mean HbA1c of group A (7.80%) was significantly raised than group B (5.17%). The mean C-peptide levels in group A was significantly higher than those in group B, 1.67 mmol/l and 0.55 mmol/l, respectively. About 97% of the participants in Group A exhibited elevated serum C-peptide levels, compared to 30% of the subjects in Group B. Conclusion: In contrast to glycemic state, C-peptide appears to be a better indicator of endogenous insulin production and/or insulin resistance. These findings provide support to the notion that raising serum C-peptide and HbA1c levels can aid in the detection and management of diabetes mellitus, particularly when combined with oral hypoglycemic medications. JCMCTA 2023 ; 34 (2) : 46-50